2013
DOI: 10.21307/sjcapp-2014-009
|View full text |Cite
|
Sign up to set email alerts
|

How do Girls with Low Functioning Autism Compare to Boys with Autism and Typically Developing Girls with regard to Behavior, Cognition, and Psychopathology?

Abstract: Background: The female autism spectrum disorder (ASD) phenotype is currently underresearched. Girls with ASD may differ from boys with ASD, yet few studies have tested this hypothesis, particularly among low functioning individuals. This study compared girls and boys with predominantly low functioning ASD and typically developing girls during middle and late childhood across autism symptoms, cognition, sensory overresponsivity, and co-occurring psychopathology. Methods: Three mental-age-matched groups were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…At the behavioral level, we found that males and females with ASD did not show sex differences in SOR symptom severity, which is consistent with a number of other studies [Mandy et al 2012;Bitsika et al, 2018;Nguyen & Ronald, 2014]. Although one study [Kumazaki et al, 2015] reported greater sensory issues in females compared to males with ASD, these participants were younger than in the current study, suggesting a need to examine sex differences in sensory processing across development.…”
Section: Discussionsupporting
confidence: 91%
“…At the behavioral level, we found that males and females with ASD did not show sex differences in SOR symptom severity, which is consistent with a number of other studies [Mandy et al 2012;Bitsika et al, 2018;Nguyen & Ronald, 2014]. Although one study [Kumazaki et al, 2015] reported greater sensory issues in females compared to males with ASD, these participants were younger than in the current study, suggesting a need to examine sex differences in sensory processing across development.…”
Section: Discussionsupporting
confidence: 91%
“…Another study examining predominately low functioning ASD girls and boys found no sex differences in autistic symptoms (i.e. restricted behavior, sensory over-responsivity, social cognition, and psychopathology), but did find sex differences in attention to detail (Nguyen and Ronald 2014). Several other studies have indicated that sex differences in perception, eye-hand integration, and communication disappear when IQ is controlled (Lord, Schopler et al 1982, Banach, Thompson et al 2009).…”
Section: Sex Differences In Autistic Diagnosis and Phenotypementioning
confidence: 95%
“…A few studies have concluded that no sex differences exist on some specific domains of ASD (Pilowsky, Yirmiya et al 1998, Rivet and Matson 2011, Worley and Matson 2011, Nguyen and Ronald 2014, Reinhardt, Wetherby et al 2015). For instance, one study discovered that no sex differences exist in psychopathology of high functioning ASD children, although the ASD group exhibited higher psychiatric symptoms than the control (Worley and Matson 2011).…”
Section: Sex Differences In Autistic Diagnosis and Phenotypementioning
confidence: 99%